2002
DOI: 10.1021/bi025908b
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Copper (II) on the Cytochrome P450 Enzymes and NADPH−Cytochrome P450 Reductase:  Inhibition of Cytochrome P450-Catalyzed Reactions by Copper (II) Ion

Abstract: Inhibitory effects of Cu(2+) on the cytochrome P450 (P450)-catalyzed reactions of liver microsomes and reconstituted systems containing purified P450 and NADPH-P450 reductase (NPR) were seen. However, Zn(2+), Mg(2+), Mn(2+), Ca(2+), and Co(2+) had no apparent effects on the activities of microsomal P450s. Cu(2+) inhibited the reactions catalyzed by purified P450s 1A2 and 3A4 with IC(50) values of 5.7 and 8.4 microM, respectively. Cu(2+) also inhibited reduction of cytochrome c by NPR (IC(50) value of 5.8 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 42 publications
(60 reference statements)
1
28
0
2
Order By: Relevance
“…Since no reducing agent with enough reducing potential for the reduction of Cu 2+ to Cu + is present in our experiments of Cu 2+ binding to GSH, our data suggest that the complex Cu 2+ -GSH can also occur in vitro. Kim et al (2002) have reported that inhibition of the CYP450 system activity by copper ions is the result of structural changes in CYP450 reductase, which would prevent the effi cient electron transfer within the system. Although we cannot exclude this possibility, our data indicate that interaction of CYP450 monooxygenase with Cu 2+ also results in structural changes that would contribute to the inhibition of the whole system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since no reducing agent with enough reducing potential for the reduction of Cu 2+ to Cu + is present in our experiments of Cu 2+ binding to GSH, our data suggest that the complex Cu 2+ -GSH can also occur in vitro. Kim et al (2002) have reported that inhibition of the CYP450 system activity by copper ions is the result of structural changes in CYP450 reductase, which would prevent the effi cient electron transfer within the system. Although we cannot exclude this possibility, our data indicate that interaction of CYP450 monooxygenase with Cu 2+ also results in structural changes that would contribute to the inhibition of the whole system.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot exclude this possibility, our data indicate that interaction of CYP450 monooxygenase with Cu 2+ also results in structural changes that would contribute to the inhibition of the whole system. It is noteworthy that the CYP450 reductase catalyzes the second step in the catalytic cycle of the CYP450 system (Slepneva et al, 1995;Kim et al, 2002). Being the fi rst and limiting step in such cycle, structural changes of the monooxygenase, which lead to the impairment of the monooxygenase-substrate complex, are likely to contribute more signifi cantly to the inhibition of the system than structural changes in the reductase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may possibly be due to the inhibition by copper of cytochrome p450 catalysed reactions. Kim et al (2002) found a 30 µM dose of CuCl 2 completely depressed cytochrome P450 activity in an in vitro assay. As the granulosa cell culture has testosterone substrate in the media it therefore relies only on cytochrome P450 aromatase activity, whereas the theca cell culture relies on de novo synthesis of steroids and therefore many cytochrome P450 catalysts.…”
Section: Discussionmentioning
confidence: 92%
“…In HepG2 cells, Cu 2+ was able to increase CYP1A1 mRNA in a time-and dose-dependent manner [159] and potentiated the inducing effect of TCDD on CYP1A1 protein and catalytic activity levels [128]. Previous studies by Kim et al [160] have reported that Cu 2+ inhibited the hepatic microsomal CYP450 catalyzed reactions in mice and rats as a result of impaired NADPH-P450 reductase. In addition, it has been reported that Cu 2+ deficiency increased CYP1A1 activity in rat small intestine [161], implying a suppressive effect of Cu 2+ on CYP1A1.…”
Section: Cu 2+mentioning
confidence: 91%